Handbook of research on creativity and innovation - Zhou, Jing; Rouse, Elizabeth D. (Research handbooks in business and management series, 2021)
"This cutting-edge Handbook takes stock of a diverse set of theoretical and methodological perspectives that address creativity, innovation, and the ways in which they intersect. Considering the development of the field, the Handbook examines current trends to chart a path forward for promising future research. Leading international contributors showcase some of the most advanced and interesting work in the creativity and innovation field, providing a platform for idea exchange and cross-fertilization. Reviewing the foundations for conducting rigorous creativity research, chapters elaborate on theoretical models that explain both individual and team creativity and innovation, and discuss the relationship between creativity and standardization. The Handbook also analyzes the role of social influences in the processes of creativity and innovation, as well as how to make sense of and study creativity and innovation. In doing so, the Handbook highlights both quantitative and qualitative research methods for conducting creativity-innovation research. Presenting an expert analysis of research on creativity and innovation, this Handbook will be a vital reference point for scholars and students in these fields, in addition to the areas of organizational innovation and organizational behavior. It will also be useful for practicing managers interested in understanding creativity and innovation"--